A review of telephone consultations for head and neck cancer follow up: a patient satisfaction survey. Issue 9 (23rd September 2021) - Stewart, R; Collins, L; Kerr, B; Gray, G; Devlin, B; Black, M; Ullah, R
Abstract: Objective: To review patient satisfaction with the change in practice towards telephone consultations during and after the coronavirus disease 2019 pandemic for head and neck cancer follow up. Method: A retrospective analysis was conducted of head and neck cancer telephone appointments during a six-month period in a tertiary referral centre. Results: Patients found the telephone consultations beneficial (98 per cent), with 30 per cent stating they were relieved to not have to attend hospital. Patients who travelled further, those with lower stage disease and patients with a greater interval from initial treatment were most satisfied with the telephone consultations. Sixty-eight per cent of patients stated they would be happy to have telephone consultations as part of their regular follow up after the pandemic. Conclusion: Patients found the telephone consultations beneficial and 30 per cent considered them preferable to face-to-face appointments. This study demonstrates that telephone consultations can be used as an adjunct to face-to-face appointments in an effort to reduce hospital attendances whilst maintaining close follow up.